Análise da variabilidade genética e parentesco de Lycalopex vetulus (LUND, 1842), de uma região de cerrado do norte de Minas Gerais e sudeste de Goiás – Brasil - Silva, André Pereira da (2015)
This study describes the genetic diversity of a population of Hoary foxes (Lycalopex vetulus), animal whose habitat is in the physiognomy of Cerrado, one of the most fragmented and disturbed areas of Brazil. To this end, 33 individuals were captured in a region of cattle ranches in northern Minas Gerais and southeast of Goiás. We amplified 10 microsatellite loci. Our data reveal that these loci are useful in the study of genetic conservation. The genetic diversity present in individuals captured in this study, can be considered high, despite the high degree of fragmentation in the area. The effective population size calculated in this study shows that the genetic diversity supported by the animals studied is representative of a population of approximately 1,300 individuals. We conducted kinship estimates using three methods, one by reading the genotype by software, another through information obtained by field observation studies and a final one, used only when the first two were at odds, based on par visual analysis to analyze all alleles of all loci. With the aid of GPS, the distance between related individuals, paying attention to possible gender’s variation. We conclude that the fox is able to move long distances (over thirty kilometers) and that apparently there is no difference in the male and female dispersal capacity.